2019
DOI: 10.1080/0361073x.2019.1609163
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Weather Information in Younger and Older Adults: Tests of Verbatim and Gist Memory

Abstract: Background/Study Context: Memory for specific, verbatim details tends to decline with age, and reliance on gist-based information increases. However, instructions that direct attention toward certain types of information can benefit memory accuracy for that information. Previous work has examined gist-based and verbatim memory for images, but little work has utilized stimuli that participants may study in their daily lives, such as a weather forecast. Methods:The current study examined how younger and older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 56 publications
3
19
1
Order By: Relevance
“…Based on the results of our experiment, we found further evidence to support previous research suggesting an associative memory deficit present in old age, here extending that work to associative numerical memory (Castel, 2007; Naveh-Benjamin, 2000). These results may appear to conflict with previous work demonstrating that older adults have better memory for numbers that fit a particular schema, but worse memory for items that are schema-irrelevant like over-market grocery prices (Castel, 2005; Castel et al, 2013; Gallo et al, 2019; Soederberg Miller, 2003). In the context of the current study, older adults may have more schematic support for negative and positive sentences, as they are perhaps more likely to consume this type of information in the daily news cycle than more neutral information.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Based on the results of our experiment, we found further evidence to support previous research suggesting an associative memory deficit present in old age, here extending that work to associative numerical memory (Castel, 2007; Naveh-Benjamin, 2000). These results may appear to conflict with previous work demonstrating that older adults have better memory for numbers that fit a particular schema, but worse memory for items that are schema-irrelevant like over-market grocery prices (Castel, 2005; Castel et al, 2013; Gallo et al, 2019; Soederberg Miller, 2003). In the context of the current study, older adults may have more schematic support for negative and positive sentences, as they are perhaps more likely to consume this type of information in the daily news cycle than more neutral information.…”
Section: Discussioncontrasting
confidence: 97%
“…This analysis examining lenient recall accuracy suggests that when using a gist-based measure, older adults were equally as accurate in their memory as younger adults, which supports well-established findings of older adults’ reliance on gist-based processing (Brainerd & Reyna, 2001; Gallo et al, 2019; Koutstaal, 2006; Reder et al, 1986). Unfortunately, this more lenient scoring criterion was not sensitive enough to detect the Arousal × Valence interaction, which was likely eliminated due to the more liberal measure.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…At test, participants were asked to determine which of the two items was the cheapest (i.e., gist information) or to recall the exact price (i.e., verbatim/detailed information). It was found that older adults, who presumably relied more on the gist of the stimuli, had comparable performance as young adults when choosing the cheapest item while their memory performance for the exact price was lower (Flores et al, 2017; see also Gallo, Hargis, & Castel, 2019 for comparable results).…”
Section: Discussionmentioning
confidence: 95%